Where the streams share a course: an exploration of postcolonial African urban soundscape - Obijiaku, Chidi (My University, 2020)
This research sets out to investigate how composers of Igbo choral art music (ICAM) engage with the socio-economic, political and philosophical developments in the postcolonial Nigerian urban society using hybridity as a fundamental resource to composition. Through the lenses of Igbo choral art music, the thesis interrogates the meanings of hybridity in African art music, and positions the practice as a representation of postcolonial identities in Africa.From the above standpoint, the thesisargues for anexpansion of the existing framework of hybridity in African art music through the incorporation of urban sounds as compositional resources. The study further examines aspects of postcolonial Nigerian urban cultures in the lyrics, melodic structure, subject matter, and orchestration of Igbo choral art music (ICAM)works composed between 2008 and 2018. Through the analyses of musical scores and interviews with renowned composers and choral directors of the genre like Ugochukwu Onwuka, Sam Ojukwu Alvan-Ikoku Nwamara and Ifeanyi Ikegwuonu, the research explores how ICAM employs hybridity to engagewith the socio-political and economic landscape of Nigerian urban spaces in these ten years. From the data collected using the above methods, the thesis concludes that hybridity in modern ICAM works does not only serve for artistic enrichment but also as a structure through which the composers reflect their formal music education and African cultural backgrounds. Hybridity is also a strategy which ICAM composers have carefully employed to situate their compositions within the realities of the postcolonial Nigerian urban spaces in the last decade
A portfolio submitted in partial fulfillment for the degree of Master of Music in the Wits School of Arts, Faculty of Humanities, University of the Witwatersrand, Johannesburg, 2020